Young peoples’ reflections about using a chatbot to promote their mental wellbeing in northern periphery areas - a qualitative study - Kostenius, Catrine; Lindström, Frida; Potts, Courtney; Pekkari, Niklas (International Journal of Circumpolar Health, 2024)
An international research collaboration with researchers from northern Sweden, Finland, Ireland, Northern Ireland, Scotland and developed the ChatPal chatbot to explore the possibility of a multilingual chatbot to promote mental wellbeing in people of all ages. In Sweden the end users were young people. The aim of the current study was to explore and discuss Swedish young peoples’ experiences of using a chatbot designed to promote their mental wellbeing. Young people aged 15–19 filled out an open-ended survey giving feedback on the ChatPal chatbot and their suggestions on improvements. A total of 122 survey responses were analysed. The qualitative content analysis of the survey responses resulted in three themes each containing two to three sub-themes. Theme 1, feeling as if someone is there when needed, which highlighted positive aspects regarding availability and accessibility. Theme 2, human-robot interaction has its limitations, which included aspects such as unnatural and impersonal conversations and limited content availability. Theme 3, usability can be improved, given technical errors due to lack of internet connection and difficulty navigating the chatbot were brought up as issues. The findings are discussed, and potential implications are offered for those designing and developing digital mental health technologies for young people. Validerad;2024;Nivå 2;2024-07-03 (joosat); Funder: Interreg Northern Periphery and Arctic Programme (grant number 345); Full text: CC BY-NC License